The Effect of Trade Openness on Income Inequality Selected Latin American Countries - Odeh, Omar (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
The importance of trade openness has increased after 1990s, too many countries adopted more trade open policies to improve their economies and to improve their population's living standards. At the same period, the importance of the inequality among people has also increased which was and still a topic of interest. The aim of this study is to find out the impact of trade openness on income inequality within five countries of Latin America. In other words, does trade openness have a statistically significant effect on income inequality or not? The results of the study showed that trade openness had a statistically significant negative effect on income inequality. Moreover, the unemployment had a statistically significant negative effect on income inequality while the ideology of the government had also a statistically significant effect on income inequality with a positive effect. At last, the inflation had no a statistically significant effect on income inequality. Keywords: Trade openness, Income inequality, Heckscher-Ohlin theory, Globalization, and the Ideology of government

ÖZ: Dış ticaretin önemi özellikle 1990 sonrası artmış, bir çok ülke ekonomilerini geliştirmek ve vatandaşlarının yaşam standardını yükseltmek için daha dışa açık ekonomi politikaları uygulamaya başlamıştır. Ancak bu dönem, ülkeler ve bireyler arası eşitsiz gelir dağılımının da ön plana çıktığı bir dönem olmuştur. Bireyler arasındaki gelir eşitsizliği bugün de en ilgi çeken konularda biridir. Bu çalışmada beş Latin Amerika ülkesinde dış ticare hacmi ve gelir dağılımı arasındaki ilişki incelenmiştir. Bir diğer deyişle uygulanan dışa açık büyüme modelleri nedeniyle artan dış ticaret hacminin gelir dağılımı üzerinde olumlu ya da olumsuz herhangi anlamlı bir etkisi olup olmadığı araştırılmıştır. Araştırma bulguları artan dış ticaret hacminin bu ülkelerdeki gelir dağılımını olumsuz etkilediğini göstermektedir. Artan dış ticaret hacminin yanı sıra açıklayıcı değişken olarak kullanılan işsizlik oranının ise gelir dağılımını olumsuz etkilediği tespit edilmiştir. Bir diğer açıklayıcı değişken olarak kullanılan yönetimdeki partinin benimsediği ideolojinin gelir dağılımı üzerinde etkili olduğu sonucuna ulaşılmıştır. Sol ideolojiyi benimseyen partiler döneminde dışa açık büyüme politikaları uygulanmasına ragmen uygulanan sosyal politikalar nedeniyle gelir dağılımındaki eşitsizlik azalmaktadır. Sağ ideolojiyi benimseyen partiler döneminde ise tersi bir ilişki söz konusudur. Enflasyon oranı açıklayıcı değişkeni ile gelir dağılımı arasında ise anlamlı bir ilişki bulunamamıştır. Anahtar Kelimeler: Trade openness, Income inequality, Heckscher-Ohlin theory, globalization, and the Ideology of government
Master of Science in Economics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2015. Supervisor: Assoc. Prof. Dr. Fatma Güven Lisaniler.
Keywords: Economics; Income distribution - Inequality; Economic Conditions and Developmen t- Latin American Countries; trade openness; Income inequality; Heckscher-Ohlin theory; Globalization, and the Ideology of government